Regional Economic Outlook, October 2007, Asia and Pacific. (Regional Economic Outlook, 2007)
Economic developments in Asia have been positive so far in 2007. Growth has been stronger (and in many cases more balanced) than expected across much of the region, again led by China and India, and inflation pressures remain largely contained. Moreover, Asia weathered the recent financial turbulence relatively well. The outlook is favorable, with growth expected to decline only modestly in 2008 as foreign demand for Asia's exports slows. The main risk for the region is a sharper-than-expected global slowdown.